Severe Pulmonary Vein Stenosis Resulting From Ablation for Atrial Fibrillation: Presentation, Management, and Clinical Outcomes. Issue 23 (6th December 2016) - Fender, Erin A.; Widmer, R. Jay; Hodge, David O.; Cooper, George M.; Monahan, Kristi H.; Peterson, Laurie A.; Holmes, David R.; Packer, Douglas L.
Abstract : Background: The frequency of pulmonary vein stenosis (PVS) after ablation for atrial fibrillation has decreased, but it remains a highly morbid condition. Although treatment strategies including pulmonary vein dilation and stenting have been described, the long-term impacts of these interventions are unknown. We evaluated the presentation of severe PVS, and examined the risk for restenosis after intervention using either balloon angioplasty (BA) alone or BA with stenting. Methods: This was a prospective, observational study of 124 patients with severe PVS evaluated between 2000 and 2014. Results: All 124 patients were identified as having severe PVS by computed tomography in 219 veins. One hundred two patients (82%) were symptomatic at diagnosis. The most common symptoms were dyspnea (67%), cough (45%), fatigue (45%), and decreased exercise tolerance (45%). Twenty-seven percent of patients experienced hemoptysis. Ninety-two veins were treated with BA, 86 were treated with stenting, and 41 veins were not treated. A 94% acute procedural success rate was observed and did not differ by initial management. Major procedural complications occurred in 4 of the 113 patients (3.5%) who underwent invasive assessment, and minor complications occurred in 15 patients (13.3%). Overall, 42% of veins developed restenosis including 27% of veins (n=23) treated with stenting and 57% of veins (n=52) treated with BA. The 3-year overall rate of restenosis was 37%, with 49% of BA-treated veins and 25% of stented veins developing restenosis (hazard ratio, 2.77; 95% confidence interval, 1.72–4.45; P <0.001). After adjustment for age, CHA2DS2-VASc score, hypertension, and the time period of the study, there was still a significant difference in the risk of restenosis for BA versus stenting (hazard ratio, 2.46; 95% confidence interval, 1.47–4.12; P <0.001). Conclusions: The diagnosis of PVS is challenging because of nonspecific symptoms and the need for dedicated pulmonary vein imaging. There is no difference in acute success by type of initial intervention; however, stenting significantly reduces the risk of subsequent pulmonary vein restenosis in comparison with BA. Abstract : Supplemental Digital Content is available in the text.